A Retrospective Naturalistic Study Comparing the Efficacy of Ketamine and Repetitive Transcranial Magnetic Stimulation for Treatment-Resistant Depression - Georgios Mikellides; Georgios Mikellides; Panayiota Michael; Lilia Psalta; Lilia Psalta; Teresa Schuhmann; Alexander T. Sack; Alexander T. Sack (Frontiers in Psychiatry, 2022)
Depression is a common mental disorder that affects many people worldwide, while a significant proportion of patients remain non-responsive to antidepressant medications. Alternative treatment options such as ketamine therapy and repetitive transcranial magnetic stimulation (rTMS) therapy are offered nowadays. This study aims to describe and compare the acute antidepressive efficacy of both, intramuscular ketamine and rTMS in depression patients seeking help in a naturalistic clinical mental health setting. The clinical records of 24 patients with treatment resistant depression were collected from the clinical base of a real life clinic. Twelve patients were treated with intramuscular ketamine, twice weekly for 8 sessions, and twelve patients were treated with 30 sessions of left dorsolateral prefrontal cortex – intermittent theta-burst stimulation (DLPFC-iTBS). Using three clinical assessments (HDRS, HAM-A, BDI-II), our data reveal that both therapies led to significant improvement in symptoms from pre- to post- treatment, as well as that the two experimental groups did not differ significantly with respect to pre- to post- depressive and anxiety symptoms, indicating that the effect of both experimental groups in our sample was equally effective. Furthermore, our results showed high remission and response rates in both groups, with no statistical differences between the patients of ketamine group and rTMS group in remission and response rates. We show a significant pre- to post- treatment reduction in depressive and anxiety symptoms, with no significant differences between the two experimental groups, indicating that the effect of both therapies was equally effective in our limited sample.